Evaluating Black Soldier Fly (Hermetia illucens (L.) Residues from Various Organic Feedstocks as Organic Fertilizers for Sweet Corn Cultivation in Thailand - Tussanakit, Supphawed; Chungopast, Sirinapa; Kaewtapee, Chanwit; Masmeatathip, Roungthip; Matsumoto, Yoshiki; Kawasaki, Kiyonori; Nomura, Mika (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2025)
Black soldier fly (BSF, Hermetia illucens (L.)) cultivation produces residues that can serve as valuable sources of organic matter. In this study, we used five organic materials—chicken feed, tofu meal, pineapple peel, cassava meal, and dry chicken manure—as feed for BSF larvae. The nutrient content and properties of the resulting residues for sweet corn cultivation were analyzed. The highest decomposition rate was observed with tofu meal, at 46.46 mg day-1. Residues from BSF larvae fed chicken feed were the richest in nitrogen at 3.75%. Residues from larvae fed dry chicken manure and pineapple peel contained the highest levels of phosphorus and potassium at 4.88% and 5.17%, respectively. All treatments, except for those with dry chicken manure, showed extremely high levels of organic matter in the range of 32.56–83.52%. Notably, residues from BSF larvae fed cassava meal exhibited the highest seed germination index at 94.87% as well as the highest unhusked ear weight, at 437.10 kg ha-1 and husked ear length, at 18.47 cm. These results showed that the use of BSF residues improved the growth and yield of sweet corn. Thus, these findings suggest the potential for using BSF-derived organic fertilizers in sweet corn cultivation in Thailand.